History and approaches to heritage studies - Messenger, Phyllis Mauch, 1950-; Bender, Susan J.; Shackel, Paul A. (Cultural heritage studies., 2019)
This volume contributes to scholarship on the theory and practice of heritage, with a focus on pedagogy. It is an important collection at the intersection of theory, practice, and teaching. This work intervenes in a broader discourse on the relevance of archaeology in education, and the tensions between education for democracy and justice, and the skills-based economy.